Análisis de las costumbres y tradiciones montubias para el fortalecimiento turístico en el cantón Babahoyo - Izquierdo Manzaba, Shirley Katiuska (2020)
This case study is aimed at the "Analysis of Montubias Customs and Traditions for the Tourism Strengthening of the Babahoyo canton" has the purpose of encouraging the Ancestral Interculturality in the Fluminense population, being Babahoyo's cultural value integrating and holistic, with the passing of the generations have received the phenomenon of transculturation. The project contributes to Cultural Tourism for tourism strengthening by accessing the influx and increase of tourists, Babahoyo has an unequaled ancestral cultural wealth, its festivities, myths and legends, gambling among others. The capacities to safeguard customs and traditions demonstrate the historical and cultural identity value. This project will benefit the inhabitants of the Babahoyo canton that will have the congruence of reaching new illustrations on the conservation of Cultural Heritage, helping to boost tourism and its culture through the actors involved.